Korea : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1997)
This Selected Issues paper on Korea provides background information on economic developments and policies, with particular emphasis on 1995-96. Following two years of rapid expansion, led by buoyant investment and exports, economic growth moderated in late 1995 and the first half of 1996. The moderation was in response to the earlier tightening of monetary conditions and less favorable short-term export prospects. The slowdown was reflected in a sharp deceleration in final domestic demand, whose contribution to growth fell from 9.1 percent in 1995 to 6.6 percent in the first half of 1996.